Respuesta :

Answer:

1

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

x+24+13=2x−16

x+ 1 2 + 1 3 =2x+ −1 6

(x)+( 1 2 + 1 3 )=2x+ −1 6 (Combine Like Terms)

x+ 5 6 =2x+ −1 6

x+ 5 6 =2x+ −1 6

Step 2: Subtract 2x from both sides.

x+ 5 6 −2x=2x+ −1 6 −2x

−x+ 5 6 = −1 6

Step 3: Subtract 5/6 from both sides.

−x+ 5 6 − 5 6 = −1 6 − 5 6

−x=−1

Step 4: Divide both sides by -1.

−x −1 = −1 −1

x=1

Answer:

The answer to your question is x = 1

Step-by-step explanation:

Data

Equation                                        x + 2/4 + 1/3 = 2x - 1/6

-Subtract 2x in both sides           x + 2/4 + 1/3 -2x = 2x - 2x -1/6

-Simplify                                        - x + 2/4 + 1/3 = -1/6

-Subtract 2/4 and 1/3 in both sides -x + 2/4 - 2/4 + 1/3 - 1/3 = -1/6 - 2/4 - 1/3

-Simplify                                         -x = -1/6 - 2/4 - 1/3

                                                      -x = (-2 - 6 - 4)/12

                                                     -x = -12/12

                                                     -x = -1

-Result                                           x = 1